Necessidade de reanimação neonatal e fatores associados em maternidade de baixo risco de Sergipe - Amorim, Fernanda Oliveira de (2019)
Objectives: This study aims to evaluate the panorama of neonatal resuscitation in a low-risk maternity in Sergipe, as well as the association between the need for resuscitation, the outcome of the newborns submitted to these maneuvers, and maternal, obstetric and fetal risk variables related mainly to sociodemographic and perinatal care aspects. Methods: This is an observational, analytical, case-control study based on the evaluation of neonatal resuscitation cases that occurred between September and December 2018 in a maternity in Sergipe. All the newborns that needed neonatal resuscitation in this period were defined cases. For each case, three controls were selected. From then on, the existence of a risk association between maternal, obstetric and fetal variables and the need for neonatal resuscitation, as well as of such variables and worse post-resuscitation outcomes, were analyzed. Results: The variables living in rural areas (p = 0.04) and gestational age less than 39 weeks (p = 0.001) presented a significant risk association with the need of neonatal resuscitation. Being small for gestational age correlated with worse post-resuscitation outcomes - transference and death - for the newborn (p = 0.047), while prenatal (p = 0.021) was statistically associated with a more favorable outcomes for reanimated RNs. Conclusions: The results indicate the need for a revision of the care model to the newborn, from prenatal to birth.